Breath odors origin, diagnosis, and management - Sterer, Nir (Springer, 2011)
Bad breath is a common and embarrassing problem. About 20% of adults suffer from bad breath on a day-to-day basis, and millions more worry about having it. In some cases, telltale breath odors can provide important clues regarding specific diseases. Yet, despite the prevalence and significance of bad breath, most health professionals still know little about its origins, diagnosis, and treatment. The past fifteen years have witnessed rapid development in research into bad breath. Investigators have studied how bad breath is caused, where the odors originate, and which bacteria and gases are involved. Predisposing dental and medical risk factors have been identified. Novel in vitro systems and measurement techniques have been proposed, and clinical studies conducted to compare new and traditional treatments. This illustrated text presents, for the first time, a comprehensive and cohesive science-based approach to bad breath, combining basic research with clinical approaches to diagnosis and treatment. All aspects of the subject are examined thoroughly and critically, including the psychological impact of breath odor and future prospects. The authors draw upon more than thirty years? combined experience in the field, both in the laboratory and as consultants to thousands of patients in Canada, the US, the UK, and elsewhere.